Investigation of Multiple Configuration Transmitter of FSO link for Ground to Train Communication in Straight Track Model - Maisara Othman,; Mariyam Jamilah Homam,; Mohammad Faiz Liew Abdullah,; Wafi Adam Bakhit Mabrouk, (International Journal of Integrated Engineering, 2024)
There is an increasing demand for high-speed train (HSR) services. Consequently, onboard high-speed internet access needs increased as passengers travel to and from work. This sudden surge in demand introduced new challenges in delivering a seamless internet connection on-board fast-moving train. Free Space Optical (FSO) Communications technology promises a bright future for various applications, due to its cost-effectiveness, ease of deployment, and huge unregulated bandwidth, which gives it an edge over contemporary technologies. However, there is a lack of significant research on FSO links for railway communications. In this paper, straight track for FSO Ground-to-train (G2TFSO) links have been designed to overcome this mentioned issue and satisfy increased demand. G2T-FSO links feature base stations located beside the track to provide a line of sight (LOS) link for traveling trains. In this research, FSO links comprise of intensity-modulated transmitters with direct detection receiver, that utilize return zero (RZ) and non-return zero (NRZ) on-off keying (OOK) modulation formats at 2.5 Gbps, with multiple transmitters concept has been implemented to enhance the link performance, using single, dual, triple, and quad transmitters. Furthermore, the track geometrical parameters have been optimized to achieve optimal link performance. The measured meteorological data obtained from the Department of Meteorology Malaysia have been incorporated to simulate rain and fog weather attenuations for Malaysia's environment. Performance evaluation on the G2T-FSO has been conducted in terms of BER at various distances and received power at different weather conditions using the Optisystem®. The findings show the moderate rain and fog weather conditions' effects provide a reasonable performance evaluation of G2T-FSO communications link for the straight track model.